2012
DOI: 10.1590/s0104-42302012000400023
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos moleculares dos esteroides sexuais sobre a cartilagem e os ossos

Abstract: In Brazil, the increase in the reported cases of degenerative diseases of articular cartilage is 20% per year, meaning that 200,000 Brazilians develop degenerative joint diseases every year, which have a negative impact on bone mass. This study shows evidence that hormone production of sexual steroids (estrogens, progestogens, and androgens) have an influence on cartilage quality, as well as on bone mass. Therefore, this review aimed to analyze literature data on the molecular and genic action of sexual steroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
2
0
3
Order By: Relevance
“…However, in some small rodents, such as rats, the growth plate is maintained, showing continued longitudinal growth throughout the lifespan of the animal. In older rats, the growth plate structure and thickness is maintained but is not functional and longitudinal growth ceases at a certain point ( 28 31 ). For this reason, the rat model may be helpful in evaluating the effects of GS on the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some small rodents, such as rats, the growth plate is maintained, showing continued longitudinal growth throughout the lifespan of the animal. In older rats, the growth plate structure and thickness is maintained but is not functional and longitudinal growth ceases at a certain point ( 28 31 ). For this reason, the rat model may be helpful in evaluating the effects of GS on the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The progestins present in the composition of the COCs used, drospirenone and desogestrel, are known to act on androgen receptors by competitive inhibition, with this mechanism resulting in important antiandrogenic effects on bone metabolism since testosterone plays a key role in bone mass acquisition. [ 27 ] Hadji et al [ 28 ] found no effect on the fracture risk of users of contraceptives containing only progestin, demonstrating the preservation of bone mass. Thus, the effect of progestin on bone metabolism may be associated with its combination with the estrogen component, either 17β-estradiol or EE, and with the route of administration, either oral or transdermal.…”
Section: Discussionmentioning
confidence: 99%
“…A incidência da osteoartrite em mulheres tem relação com o estrogênio, um importante hormônio que desempenha papel na manutenção da homeostase dos tecidos articulares (PACCA et al, 2018), que na fase da menopausa, geralmente entre 45-55 anos de idade, há redução em sua produção de forma progressiva, acarretando perdas funcionais, a exemplo do tecido ósseo, com aumento da atividade dos osteoblastos, inibição da retirada de cálcio do organismo e diminuição da formação e atividade dos osteoclastos, degeneração articular, entre outras (WOLFF et al, 2012).…”
Section: Discussionunclassified